APPLYING THE INSIDE-OUTSIDE CIRCLE (IOC) TOWARDS STUDENTS’ SPEAKING ABILITYAT THE SECOND GRADE OF SMA INSHAFUDDIN - Nurul Kamaliah (English Education Department, 2018)
This study is based on the problem of the low speaking skill at the eleventh grade students of SMA Inshafuddin. The study is intended to know whether Inside-Outside Circle (IOC) can improve the students’ ability. It also focused to know what the responses of the students are when Inside-Outside Circle (IOC) is applied in speaking class.The subject of the study was the second grade class XI IPA of SMA Inshafuddin. This study usedpre-experimental research by focusing on one group pre-test and post-test design.Techniques in collecting the data weretest and questionnaire.Then, they were analyzed by using statistic calculation of t-test and percentage formula.The results of this study show that Inside-Outside Circle (IOC) can effectively improve students speaking ability. The improvement of students was obtained from the differences between pre-test and post-test. The mean score of pre-test is 66.11 and it improves to 70.11. Further, it is supported by the t-test result as the calculation value obtain t-score (4.381)> t-table (2.120). It can be concluded that there is a significant improvement of students’ speaking ability after they were taught by using Inside-Outside Circle (IOC).The result of questionnaire shows that by using Inside-Outside Circle (IOC) the students become more active to speak and interact with each other in teaching and learning process. Therefore, the result of the study implies that English teachers could applyInside-Outside Circle (IOC) technique in teaching speaking that can give students many chances to speak.